Metagenomic investigation of the fecal microbiota in Lakor goats of different sexes with a basic diet of field grass - INSUN SANGADJI; RONY MARSYAL KUNDA; PRASETYARTI UTAMI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sangadji I, Kunda RM, Utami P. 2025. Metagenomic investigation of the fecal microbiota in Lakor goats of different sexes with a basic diet of field grass. Biodiversitas 26: 1861-1869. Gut microbiota play a crucial role in the health and productivity of ruminants, including goats. This study investigated the composition and diversity of fecal microbiota in Lakor goats of different sexes fed a basic diet of field grass using a metagenomic approach. A total of 10 samples were collected from male and female goats of 5 samples each, and high-throughput sequencing of the 16S rRNA gene was performed to analyze the microbial community structure. Results revealed significant differences in microbiota composition between sexes, which may be influenced by hormonal differences, feeding behavior, and metabolic needs. This study suggests that sex influences the composition of fecal microbiota in Lakor goats. Moreover, it revealed that sex affects the diversity and composition of the microbiota, with significant differences at the family and species levels. Alpha diversity analysis showed that female goats had higher microbial diversity than male goats, with a Shannon index of 2.03 in females and 1.33 in males, indicating a more complex microbial community in females. The microbial community composition in male goats was dominated by species such as Romboutsia timonensis and Clostridium sp., whereas female goats showed a more balanced microbial distribution, with the dominance of genera such as Pradoshia, Eubacterium, and Lysinibacillus. Phylogenetic analysis showed that female goats have a more stable microbial community, supporting more efficient fiber fermentation and Short-Chain Fatty Acid (SCFA) metabolism. Proximate test results showed differences in feed nutrient content between the wet and dry seasons, with higher crude protein content in the wet season, potentially affecting feed quality and microbiota. Overall, this study highlights the importance of considering sex in microbiota studies to optimize feeding strategies and health management for Lakor goats. These findings suggest that sex-specific dietary interventions and probiotic strategies could improve feed utilization, immune function, and productivity in Lakor goats.